(untitled) (Research, Society and Development, 2020)
The work seeks to evaluate the nutritional labeling of protein supplements targeted at vegan athletes. Field and quantitative study, carried out in specialized stores and online shopping sites. The sample consisted of 25 labels of different brands, which were analyzed: flavor, vegetable protein, energy value, carbohydrate content, total fats, saturated and trans fats, fibers, vitamin B12, minerals, branched chain amino acids (BCAA) and glutamine. The legislations used for analysis were: RDC 259/2002, 359/2003, 360/2003 and 18/2010. It was found that the pea (68%) was the main vegetable source and 56% of the labels came from a combination of vegetable proteins. With regard to nutritional information, the calculated energy value was 109,8 Kcal and the contribution to carbohydrates, proteins and fats were, respectively, 10,86%, 74,39% and 14,75%. The protein contents did not present significant difference (p> 0,05) when the sources based on peas, peas with rice, soy and the isolated or combined sources were compared. As for the fiber content, 40% of the supplements were considered a source (4,68 ± 0,30 g/100 g), 36% rich (15,14 ± 3,60 g/100 g) and 12% zero fibers. Regarding micronutrients, 28% of the labels exposed vitamin B12 and iron in the nutritional information and 100% the sodium content. The presence of BCAA and glutamine was reported on 56% and 12% of labels, respectively. Thus, it was found that the nutritional information on the labels is within the recommended parameters, but it is suggested the creation of specific legislation that ensures the quality of supplements aimed at vegan athletes.